Interactive Learning untuk Pengendali PID Berbasis Website - Patricia Fernandez; Ferry Hadary; Seno Darmawan Panjaitan (Jurnal Otomasi Kontrol dan Instrumentasi, 2025)
Conventional learning methods for PID control systems demonstrate weaknesses in concept comprehension effectiveness due to lack of real-time visualization and theory-practice integration. This study aims to develop a web-based interactive learning platform integrating digital simulation with physical experiments using ESP-32. The research method employs Research and Development approach with ADDIE model including literature study, system design, platform implementation, and evaluation through beta testing with 23 Electrical Engineering students. The platform utilizes ESP-32, DC motor, rotary encoder, BTS 7960 driver, and web interface using HTML, Tailwind CSS, and JavaScript for real-time PID parameter control via WebSocket protocol. Evaluation results show average pre-test and post-test score improvement of 34.7% with paired t-test analysis p < 0.01. The platform achieves ±2% measurement accuracy, 45ms communication latency, and 99.2% WebSocket stability. Quality assessment yields feasibility score 4.2/5.0, practicality 4.0/5.0, and effectiveness 4.3/5.0. The platform significantly improves PID control concept understanding compared to conventional methods.